2010
DOI: 10.1016/j.marenvres.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between PAH biotransformation as measured by biliary metabolites and EROD activity, and genotoxicity in juveniles of sole (Solea solea)

Abstract: Polycylic aromatic hydrocarbons (PAHs) are ubiquitous contaminants in the marine environment. Their toxicity is mainly linked to the ability of marine species to biotransform them into reactive metabolites. PAHs are thus often detected at trace levels in animal tissues. For biomonitoring purposes, this findings have two main consequences, (i) the determination of the PAH tissue concentration is not suitable for the evaluation of individual exposure to PAHs (ii) it can explain sometimes the lack of correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 6 publications
2
17
1
Order By: Relevance
“…Contrary to the observed dose-dependent response, time-dependence responses were observed only with free 3-OH-BaP in bile. Comparable results, upon waterborne exposure to BaP, were reported in Sparus macocephalus (Wang et al 2008) and in sole (Solea solea), after dietary exposure to an equimolar mixture of BaP, pyrene, and fluoranthene (Wessel et al 2010). In contrast, when measuring total BaP metabolites as fluorescent aromatic compounds (FAC) in bile by fixed wavelength fluorescence, instead of the HPLC analysis, as in the previous studies (including this one), significant time-dependent responses after BaP waterborne exposure were reported (Boleas et al 1998;Costa et al 2011).…”
Section: Discussionsupporting
confidence: 50%
“…Contrary to the observed dose-dependent response, time-dependence responses were observed only with free 3-OH-BaP in bile. Comparable results, upon waterborne exposure to BaP, were reported in Sparus macocephalus (Wang et al 2008) and in sole (Solea solea), after dietary exposure to an equimolar mixture of BaP, pyrene, and fluoranthene (Wessel et al 2010). In contrast, when measuring total BaP metabolites as fluorescent aromatic compounds (FAC) in bile by fixed wavelength fluorescence, instead of the HPLC analysis, as in the previous studies (including this one), significant time-dependent responses after BaP waterborne exposure were reported (Boleas et al 1998;Costa et al 2011).…”
Section: Discussionsupporting
confidence: 50%
“…This is in contrast with results by e.g. Wessel et al (2010) and Hylland et al (2006), in which relationships between PAH bile metabolites and DNA damage were reported. The generalised linear model suggested that the size of the fish, but also condition (as liver-somatic index) contributed to explaining some of the variability in DNA strand breaks.…”
Section: Discussioncontrasting
confidence: 99%
“…We cannot rule out 1) the occurrence of DNA damages such as DNA-adducts and 2) that DNA damages may have occurred in other tissues, particularly in bile ducts whose cells displayed preneoplastic lesions correlated to the fraction and the dose of exposure and from which most neoplasms derived. Indeed, PAHs are known to be bioavailable and quickly metabolized by fish hepatic enzymes as confirmed here by the kinetic of cyp1a expression after feeding or, in other studies, by the rapid production of biliary PAH-metabolites after 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 exposure (Wessel et al 2010;Le Du-Lacoste et al 2013). Among these metabolites, 3hydroxybenzo[a]pyrene is believed to be one of the most genotoxic (Aas et al 2000;Ruddock et al 2003;Brinkmann et al 2010;Le Du-Lacoste et al 2013).…”
Section: Carcinogenesis Mechanismsmentioning
confidence: 92%
“…Moreover, most previous laboratory studies in fish were conducted with dissolved PAHs (Jonsson et al 2004) or PAH in sediments (Cachot et al 2007). Dietetary exposure has been more rarely explored to date (Rice et al 2000;Wessel et al 2010), especially if considering carcinogenic effects. In this context, Spitsbergen et al (Spitsbergen et al 2000a) chose to explore the long-term carcinogenic effects of high concentrations of one model PAH, DMBA, regarded as one of the most potent known PAH with dibenzo [def,p]chrysene.…”
Section: Introductionmentioning
confidence: 99%